DISTRIBUTION OF DEMOCRACY IN POLICY B. CLINTON'S ADMINISTRATIONS (1993-2001) (International relations and international law Journal, 2016)
The given article considers evolution of idea of promotiondemocracy in the U.S. foreign policy during Bill Clinton’spresidency. The collapse of the Soviet Union had createdfavorable conditions for spreading of liberal democraticprinciples and values in the world and engagement of morecountries into the orbit of democratic development. The authorreveals, that the progressive trend of supporting democracy inthe U.S. policy was combined with the interference in theinternal affairs of other states under the pretext of protectinghuman rights and democracy promotion.
Keywords: democracy; B. Clinton policy